The potter's field [compact disc, unabridged] - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2011)
An unidentified corpse is found near Vigàta, a town known for its soil rich with potter's clay. Meanwhile, a woman reports the disappearance of her husband, a Colombian man with Sicilian origins who turns out to be related to a local mobster. Then Inspector Montalbano remembers the story from the Bible--Judas' betrayal, the act of remorse, and the thirty pieces of silver for the potter's field, where those of unknown or foreign origin are to be buried--and slowly, through myriad betrayals, finds his way to the solution to the crime.